Tinjauan Hukum Humaniter Mengenai Konflik Bersenjata Antara Negara Dengan Kaum Pemberontak - Basafa Asmawati Aziz Udin; Efie Baadila; Dyah Ridhul Airin Daties (Faculty of Law, Universitas Pattimura, 2022)
Introduction: International humanitarian law applies to both international and non-international armed conflicts that cause casualties. One form of armed conflict in which humanitarian law can be applied is the armed conflict between Afghanistan and the Taliban insurgents.Purposes of the Research: Analyzing and knowing the regulations regarding armed conflict between the state and the rebels, Analyzing and knowing the legal consequences for both parties to the conflict according to International Law, As one of the requirements in the completion of studies at the Faculty of Law of Pattimura UniversityMethods of the Research: This study uses a normative juridical legal research method, using primary, secondary, and tertiary legal sources and the collection of legal materials is carried out using library techniques. Furthermore, the analysis technique is carried out by thoroughly evaluating legal materials related to the issues discussed and interpreting laws or regulations related to the issues discussed.Results of the Research:it can be concluded that in international humanitarian law the regulation of armed conflict between states and rebels can be seen in Article 3 of the Geneva Conventions of 1949 and Additional Protocol II of 1977. As well as the legal consequences for the state and the rebels involved in the conflict in Afghanistan where both the Afghan state and the Taliban are subjects of international law, both of them must comply with humanitarian law and are prohibited from taking coercive actions, both physical and spiritual, to obtain information; cause physical suffering; impose collective punishment; perpetrate intimidation, terrorism and robbery; retaliation against civilians; Arresting people to be held as hostages.